Pengaruh Media Digital Interaktif Eduma terhadap Pemahaman Konsep Alam Semesta Anak Usia 5-6 Tahun - Rahma Sukmara Putri; Qonita Qonita; Taopik Rahman (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study examines the effect of the interactive digital media Eduma on children’s understanding of universe concepts aged 5–6 years at TK Nurul Hikmah Sejahtera. The study uses a quantitative approach with a quasi-experimental one-group pretest–posttest design involving experimental and control groups. Data were collected through test sheets and observation instruments and analyzed using descriptive statistics, normality test, homogeneity test, paired sample t-test, independent sample t-test, and N-Gain analysis. The results show that the use of Eduma significantly improves children’s understanding of universe concepts, with higher posttest scores in the experimental group compared to the control group. The N-Gain score of the experimental group is also categorized as high, indicating effective learning improvement. The findings imply that interactive digital media such as Eduma can be effectively integrated into early childhood learning to enhance cognitive development, especially in understanding abstract scientific concepts like the universe. Teachers are encouraged to adopt interactive and visual-based digital learning media to increase student engagement and learning outcomes